Dysregulation of the HOTAIR-miR-152-CAMKIIα Axis in Craniosynostosis Results in Impaired Osteoclast Differentiation - Dong, Chenbin; Liu, Xiangqi; Li, Jun; Lan, Dongyi; Zheng, Shan (Frontiers in Genetics, 2022)
Craniosynostosis is one of the most common craniofacial deformities demanding surgical treatment in infancy. LncRNA HOTAIR has verified its important role in osteogenesis and osteoarthritis. However, whether HOTAIR plays an essential role in the development of craniosynostosis is still unclear. In this study, we aimed to investigate the molecular role of HOTAIR in the osteoclast function and development of craniosynostosis.For osteoclast differentiation, RAW264.7 cells were induced by 50ng/mL of RANKL and 10ng/mL M-CSF, followed by TRAP staining. Cell proliferation and apoptosis were assayed by the CCK-8 kit and Annexin V-FITC apoptosis detection kit, respectively. The expression of HOTAIR was determined in PBMCs by qRT-PCR. Protein levels of all those involved genes were measured by Western blot assay. A luciferase reporter assay was used to determine the miRNA target validation. The HOTAIR expression in PBMCs from children with craniosynostosis was significantly downregulated. The results of cell proliferation and apoptosis assays indicated that silencing of HOTAIR could inhibit osteoclast differentiation and increase cell apoptosis. Moreover, the luciferase reporter assay revealed that the regulatory axis and HOTAIR-miR-152-CAMKIIα were the regulatory mechanisms of HOTAIR in the osteoclast function and development of craniosynostosis.In this study, our data showed that HOTAIR could promote osteoclast differentiation by binding miR-152. Furthermore, the HOTAIR/HOTAIR-miR-152-CAMKIIα axis was found to regulate osteoclast differentiation. These results indicate that the HOTAIR plays a crucial role in the development of osteoclasts.